(untitled) (KULT_online, 2017)
The volume “Postcolonial Political Science”, edited by Aram Ziai, Professor for Development and Postcolonial Studies at the University of Kassel, is the first collection to assemble a huge variety of innovative postcolonial interventions in the discipline of German political sciences. Besides its programmatic perspective, theoretical and empirical research is well-balanced in this collection of essays by German-speaking postcolonial scholars. Following postcolonial interventions in German sociology, history, and cultural sciences, this edition now introduces the task of decolonizing German political sciences.